KARAKTER AGRONOMI BEBERAPA PADI LOKAL ACEH - Mita Setyowati; Jekki Irawan; Leni Marlina (Jurnal Agrotek Lestari, 2018)
This research aimed to identify the agronomy character of local rice genotype of Aceh as morphological characteristic. The research conducted at the Experimental Garden of Teuku Umar University, Meulaboh West Aceh from September 2016 to March 2017. The materials used in this research are 5 local accessions of local gogo rice of Aceh: Ramos, Dewi, Sigupai, Tinggong, Siputeh, and IR 64 as control. This research used observation method. The growth and production data were presented and analyzed in graphical form. The visual observation data was presented in the form of documentary photographs and described in descriptions. The results showed that the longest plant length at age 20 days after planting (HST), 40 HST, and 60 HST was found in local accession compared to IR 64 varieties. The tillers per clums age of 20 HST were found in Siputeh local accession, while at age 40 HST and 60 HST local accessions were the least number of tillers compared to IR 64 varieties. Long panicle (Dewi), weight of pithy grain (Ramos) and percentage of pithy grain  (Ramos), percentage of empty grain (Ramos), of all best variables are found in local accessions in comparison with IR 64 varieties. The flowering age, weight of 1000 grains, and the number of productive tillers at local accessions are lower than that of IR 64 varieties. Keywords: Character of Agronomy, Gogo Rice, Local Aceh